Impact of enhanced recovery after surgery concept process optimization on the perioperative period of gynecologic laparoscopic surgery - Ou Jin; Tiebing Xu; Juan Lai; Junxia He; Yongfeng Wu; Xiaomin Yang (BMC Women's Health)
Abstract Background To explore the impact of enhanced recovery after surgery (ERAS) optimization concept process on the perioperative period of gynecologic laparoscopic surgery. Methods This retrospective observational study included patients who underwent gynecologic laparoscopic surgery based on ERAS concept process optimization (ERAS group) for uterine fibroids, adenomyosis, and ovarian cysts at Jiaxing Hospital of Traditional Chinese Medicine between January 2023 and December 2023. Patients who underwent the same laparoscopic protocol without ERAS concept process optimization between January 2022 and December 2022 were matched as the control group (non-ERAS group). Postoperative indexes and patient satisfaction were compared between the two groups. Results A total of 120 patients were included, with 60 of who underwent gynecologic laparoscopic surgery (total laparoscopic hysterectomy, TLH: n = 20; laparoscopic myomectomy, LM: n = 20; laparoscopic ovarian cystectomy, LOC: n = 20) based on ERAS (ERAS group), and the other 60 of who underwent gynecologic laparoscopic surgery (TLH: n = 20, LM: n = 20, LOC: n = 20) without ERAS (non-ERAS). In patients received gynecologic laparoscopic surgery of ERAS group, the time of first postoperative gas evacuation, the time of semi-liquid recovery, the time of urination, the time of incision pain, and the length of hospital stay were significantly shorter (all P < 0.001), and the number of nausea and vomiting was significantly reduced (all P < 0.001) compared with those in the non-ERAS group. Besides, satisfaction of patients receiving ERAS was significantly higher than in the non-ERAS group (TLH: P < 0.01; LM and LOC: P < 0.001). Conclusions ERAS optimization for gynecologic laparoscopic surgery improved patients’ outcomes, reduced complications, and improved patient’s satisfaction.